PENGARUH SUHU DAN WAKTU MASERASI TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK KULIT BUAH KAKAO (Theobroma cacao L.) - Ananta, Dimas Anggi; Ganda Putra, G.P.; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 2 (2021): JuniDO - 10.24843/JRMA.2021.v09.i02.p04, 2021)
Cocoa pod husk is a by-product of cocoa processing which is quite abundant and has not been used optimally. Cacao pod husk can be used more optimally by extracting, its content of polyphenol compounds which can be used as natural antioxidants. The aim of this study were to determine the effect of temperature and maceration time of cocoa pod husk extract as a source of antioxidants and to determine the best type of temperature and maceration time to produce cocoa pod husk extract as a source of antioxidants. This experiment was designed by using factorial randomized block design. The first factor was type of maceration temperature consisting of 30±2 ° C, 45±2 ° C and 60±2 ° C. The second factor was maceration time, which were done for 24, 36 and 48 h. The data were analyzed with analysis of variance and continued with the Tukey test. The results showed that the temperature and time of maceration had a very significant effect on yield, total phenolic and antioxidant capacity of cocoa pod husk extract. Interactions between treatments had a very significant effect on total phenolic and antioxidant capacity but did not significantly affect the yield of cocoa pod husk extract. The best treatment for producing cocoa pod husk extract as a source of antioxidants was using maceration temperature 60±2 ° C and maceration time for 36 h with yield characteristics 5,28±0,15%, total phenolic at 168.16±0,06 mg GAE/g and capacity antioxidant 130.94±0.84 mg GAEAC/g . Keywords: Cocoa pod husk, extraction, temperature, time, antioxidants.